Muharem, muzika oči života . Muharem, Music, the Eyes of Life - Mirkovič, Željko (Zdravkovic, Ivan Hadzi ; Mirkovič, Željko, 2005)
This low budget film followed the life-story of a blind Romany banjo player as he related his long career singing and playing on trains while somehow hiding his bigamy in a desperate effort to ensure he had an heir.